2020
DOI: 10.1139/apnm-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen and focused rehabilitation program: a feasibility study in improving upper limb motor function after stroke

Abstract: Neuroplasticity and recovery after stroke can be enhanced by a rehabilitation program pertinent to upper limb motor function exercise and mental imagery (EMI) as well as hyperbaric oxygen therapy (HBOT). We assessed the feasibility and safety of the combined approach utilizing both HBOT and EMI, and derived preliminary estimates of its efficacy. In this randomized controlled trial, twenty-seven patients with upper extremity hemiparesis 3-48 months after stroke were randomized to receive either a compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Our preliminary results confirm the effectiveness of HBOT in improving the clinic of cerebral stroke Pts [24,26]. We believe that the association of HBOT with rehabilitation physiotherapy and speech therapy is the most effective way to improve neurological symptoms [20]. On the basis of this conviction, we advised all Pts to follow this procedure.…”
Section: Hbot Recommendation In Chronic Stroke Ptssupporting
confidence: 70%
See 1 more Smart Citation
“…Our preliminary results confirm the effectiveness of HBOT in improving the clinic of cerebral stroke Pts [24,26]. We believe that the association of HBOT with rehabilitation physiotherapy and speech therapy is the most effective way to improve neurological symptoms [20]. On the basis of this conviction, we advised all Pts to follow this procedure.…”
Section: Hbot Recommendation In Chronic Stroke Ptssupporting
confidence: 70%
“…The ECHM document is from 2016. In the meantime, many papers [13][14][15][16][17][18][19][20][21][22][23][24][25] have been published in favour of HBOT, so that its level of evidence may have been increased.…”
Section: Hbot Recommendation In Chronic Stroke Ptsmentioning
confidence: 99%
“…Hyperbaricity of 2.5 ATA and 21% O2 is not enough to promote ischemic tolerance. Therefore, understanding the components of HBOT in both hyperoxia and hyperbaricity scenarios is crucial to induce tolerance against ischemic injuries [ 135 ]. Both preconditioning of HBOT and hypoxia possess similar efficacies in the neonatal brain.…”
Section: Pre-clinical Findings With Hbot Preconditioning For Strokmentioning
confidence: 99%
“…Regular HBOT preconditioning consists of 2–3 ATA with 60–90 min of exposure with 24 h intervals [ 137 , 138 , 139 ]. Effective ischemic tolerance can be developed when dosed with HBOT for 3–5 days [ 91 , 135 ]. Although, HBOT also induced neuroprotection against brain injuries, due to ischemia during a certain time frame [ 94 ], neuroprotection was achieved through biphasic time frames characterized by instant and delayed preconditioning effect [ 42 , 140 ].…”
Section: Pre-clinical Findings With Hbot Preconditioning For Strokmentioning
confidence: 99%
“…Hypertensive intracerebral hemorrhage(HICH) generally contributes to a catastrophic, life-changing damage with an incidence of approximately 150 in 100,000 worldwide annually,wherein >81.3% of these damages includes severe hemiplegia in the contr-alateral limbs [1][2][3][4].The victims with a limb motor dysfunction signi cantly lose self-help ability, placing a burden on family or forfeiting social engagement to some extent [5][6][7][8][9][10]. Traditionally,fundamental interventions to hemiplegia after HICH revolve around subsequent physical rehabilitation or physiotherapy [11][12][13][14].Nevertheless,res-ultant outcomes usually are discouraging or dissatisfactory,rousing uninterrupted quest for patient-oriented therapies.Many studies conducted in both humans and rodents have demonstrated that an injured brain cortex can re-control the contralateral limbs through a neural network remodeling across perilesional regions and contralesional hemisphere after rewiring an afferent circuit [15][16][17][18].Recently,peripheral nerve transfer,which can ignite compensational cerebral plasticity,has been exploited to rescue partial knee extension or hand prehension in patients with acute accid myelitis or central neurological diseases [19][20][21][22].Noticeably,though current neurotization stays in early stage and yet need to be polished [23,24],its highlights have activated our aspiration for its extrapolation to a lower-limb paralysis after HICH,and further interrogation of maneuvers for a dexterous motion during neurotization.…”
Section: Introductionmentioning
confidence: 99%